A comparative study to evaluate the clinical utility and performance of a new hand-held mobile electrocardiogram device - Desai, Nagaraj; S., Sunil Kumar; V., Guruprasad B.; S., Poornima K. (International Journal Of Community Medicine And Public Health, 2020)
Background: Electrocardiogram (ECG) is a non-invasive test which can provide clue for the presence of cardiac diseases. Simple, handheld devices, sufficiently miniaturized are useful for a widespread use. New devices, however, need to be compared with the standard ones for their performance in the real-world practice. Here in we report clinical utility of a handheld device. Methods: KardioscreenTM is a mobile and handheld device. It’s been approved for safety and performance standards and it has been certified for ‘Conformite Europeenne’ (CE). Using this device, a comparative blinded study with a conventional and commercially available standard 12 lead ECG machine was done. 604 ECGs recorded from 302 patients with various clinical disorders were coded and analyzed by two blinded observers. A third cardiologist adjudicated the reports. The reports were then correlated for the ECG patterns generated and with the clinical diagnosis. Computer generated measurements of various durations and intervals were also analyzed and compared. Regression analysis was used to compare the values. SPSS 21 software was used to analyze the data. Results: Kardioscreen device could provide recordings to diagnose including ST elevation (99%), non-ST elevation myocardial infarction (94.1%), chamber-hypertrophy (87%), conduction blocks (99%), and arrhythmias (96.4%), with good correlations with the comparator for pattern recognition. Also, computer generated measurements were significantly correlated with the comparator (R=0.96 for HR, R=0.82 for QRSd, R=0.86 for QT/QTc, R=0.76 for PR). Conclusions: The Kardioscreen device is a reliable tool for electrocardiographic diagnosis of common clinical cardiac disorders.